Maqashid Sharia as a Pillar of Inclusive Development: Moderation in Economic Growth Towards Poverty - Mardianto, Dedi; Khaerullah, Jawziyah; Ulvah, Samihah; Karmila, Karmila (Maliki Islamic Economics Journal, 2025)
This study examines the moderating role of Maqashid Sharia in the relationship between economic growth and poverty in selected OIC countries in Asia. It focuses on three dimensions: education (Hifz al-‘Aql), health (Hifz al-Nafs), and distributive justice (Hifz al-Mal). The sample includes Bangladesh, Indonesia, Pakistan, and Uzbekistan over the period 2014–2023. Panel data were analyzed using the Random Effect Model. The findings reveal that economic growth has a negative but statistically insignificant effect on poverty, indicating that growth has not been sufficiently inclusive. Although higher growth is associated with declining poverty, the magnitude of the effect is weak and unevenly distributed among low-income groups. Education, health, and distributive justice significantly reduce poverty directly. However, these variables do not significantly strengthen the impact of growth on poverty reduction. This reflects the limited relevance of education to labor market demands, the predominantly long-term effects of health improvements, and short-term efficiency–equity trade-offs in redistribution policies. The study underscores the need to promote inclusive growth through labor-oriented education reform, strengthened health services, and optimization of zakat and waqf instruments. Limitations include the small country sample, restricted Maqashid dimensions, and limited institutional coverage.